Plebiscitary revolution in Chili - Vicuña Navarro, Miguel (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
Given the distance that a certain time lag allows, this paper articulates a reading that links the Chilean revolt of October 2019 to the constituent process that has taken place during 2020. It is a reading that offers an interpretation ranging from the episode of the revolt and the events of the manifestations to the challenges posed by the design and drafting of a new constitutional charter in Chile. This reflection takes into consideration the challenges that currently call into question the foundations of the most conventional modern politics. One of the key points offered for this reading is the place of the plebiscitary device as a factor that allows for certain specific uses. To this end, the political function that the plebiscite has had in other scenarios and historical episodes is also taken into account.